What happens when adolescents meet complex texts? Describing moments of scaffolding textual encounters. (22nd July 2021) - Reynolds, Dan; Fisher, Whitney
Abstract: Adolescents face complex texts rich in academic language. Existing research has documented how teachers can design curriculum to scaffold students' comprehension of complex texts, but little work has documented the moments of adolescents' encounters with complex texts, and how teachers can scaffold these encounters on a moment‐to‐moment basis to advance their students' comprehension. We present data from an intervention in which six tutors were trained in an interactional scaffolding framework aligned with text complexity read complex texts with small groups of Year 12 students (age 16–17) in a US high school. Tutors used identical texts and lesson plans across groups, but each tutor scaffolded contingently to each group's needs. Findings revealed missed opportunities for deeper scaffolding when tutors failed to recognise the complexity of the text and failed to contextualise their scaffolds within the context of the passage under study. We also found examples of tutors taking different routes to scaffolding success contingent on the students' attempts. We present a menu of scaffolds to support teachers' practice and examples of the scaffolding for teachers and researchers to see how these scaffolds can help navigate complex texts.